2013
DOI: 10.1007/s00586-013-2707-7
|View full text |Cite
|
Sign up to set email alerts
|

Cervical curvature, spinal cord MRIT2 signal, and occupying ratio impact surgical approach selection in patients with ossification of the posterior longitudinal ligament

Abstract: Objective Factors impacting surgical options and outcomes in patients with cervical ossification of the posterior longitudinal ligament (OPLL) were explored. Methods A retrospective analysis was conducted of 127 eligible cervical OPLL patients (61 males, 66 females) aged 41-70 years (mean 55.2 years) selected from 152 total OPLL patients treated from 2002 to 2006, with 5-10-year (mean 6.8 years) follow-up. Patients underwent anterior subtotal corpectomy with ossification ligament resection (anterior surgery, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 24 publications
(31 reference statements)
1
43
0
Order By: Relevance
“…1). 2,3,8,16,18,19,21,22,28 The basic characteristics of included studies are shown in Table 1. No statistically significant differences were found in age, sex, occupying ratio of OPLL, and follow-up time between the 2 groups.…”
Section: Results Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 2,3,8,16,18,19,21,22,28 The basic characteristics of included studies are shown in Table 1. No statistically significant differences were found in age, sex, occupying ratio of OPLL, and follow-up time between the 2 groups.…”
Section: Results Search Resultsmentioning
confidence: 99%
“…Quality assessment of the included studies was independently conducted by 2 investigators, and arguments were resolved by discussion. Of the 10 nonrandomized controlled studies, 9 2,3,8,16,19,21,22,27,28 received more than 7 stars on the NOS and the 1 remaining study 18 received 6 stars. These ratings meant that all included studies were of relatively high quality.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…They recommended that surgical treatment should be provided before the advent of intramedullary spinal cord changes in signal intensity on MRI. Liu et al [5] also suggested that preoperative assessment of cervical curvature, MRIT2 signal, and occupying ratio can be used to guide clinical surgical approach selection to potentially produce better long-term outcomes in patients with OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathomechanism of cervical myelopathy caused by C-OPLL remains unknown. Despite spinal stenosis (6 mm \ space available for the spinal cord \14 mm), myelopathy may not develop in patients with the severe limitation of range of cervical spine [5]. This indicates that not only static factors but also dynamic factors, such as listhesis or hypermobility at the discontinuity of the ossified lesion, play important roles in the development of myelopathy, especially in mixed and segmental OPLL.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that spinal cord cross-sectional area (SCCSA) slowly becomes narrower in patients with OPLL, but the influence of dynamic factors may be another important factor in cervical myelopathy. Liu et al 23 found that in patients with severely limited range of movement in the cervical spine, cervical myelopathy does not always develop despite spinal stenosis (6 mm < space available for the spinal cord < 14 mm). This indicates that in addition to static factors, dynamic factors such as listhesis or hypermobility at the discontinuity of the ossified part also play important roles in the development of myelopathy, especially in mixed and segmental OPLL.…”
Section: The Radiological Parameters For Deciding the Optimal Surgicamentioning
confidence: 99%